Twin Domain Structure in Magnetically Doped Bi2Se3 Topological Insulator - Šebesta, Jakub; Carva, Karel; Kriegner, Dominik; Honolka, Jan (Nanomaterials (Basel, Switzerland), 2020)
Twin domains are naturally present in the topological insulator Bi2Se3 and strongly affect its properties. While studies of their behavior in an otherwise ideal Bi2Se3 structure exist, little is known about their possible interaction with other defects. Extra information is needed, especially for the case of an artificial perturbation of topological insulator states by magnetic doping, which has attracted a lot of attention recently. Employing ab initio calculations based on a layered Green's function formalism, we study the interaction between twin planes in Bi2Se3. We show the influence of various magnetic and nonmagnetic chemical defects on the twin plane formation energy and discuss the related modification of their distribution. Furthermore, we examine the change of the dopants' magnetic properties at sites in the vicinity of a twin plane, and the dopants' preference to occupy such sites. Our results suggest that twin planes repel each other at least over a vertical distance of 3-4 nm. However, in the presence of magnetic Mn or Fe defects, a close twin plane placement is preferred. Furthermore, calculated twin plane formation energies indicate that in this situation their formation becomes suppressed. Finally, we discuss the influence of twin planes on the surface band gap.
Keywords: magnetic doping; ab initio; topological insulators; defects